2014
DOI: 10.1534/genetics.113.161075
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin Position Effects on Circularized Sex Chromosomes Cause Filicidal Embryonic Lethality in Drosophila melanogaster

Abstract: Some circularized X-Y chromosomes in Drosophila melanogaster are mitotically unstable and induce early embryonic lethality, but the genetic basis is unknown. Our experiments suggest that a large region of X-linked satellite DNA causes anaphase bridges and lethality when placed into a new heterochromatic environment within certain circularized X-Y chromosomes. These results reveal that repetitive sequences can be incompatible with one another in cis. The lethal phenotype also bears a remarkable resemblance to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Our results here show that a large difference in abundance of the AATAT satellite between D. simulans and D. melanogaster chromosome 4s does not result in similarly dramatic levels of meiotic drive. We suggest that location as well as abundance influences whether satellite DNA blocks affect centromere behavior or take on neocentromere function, analogous to heterochromatin position effects that are proposed to influence whether or not circularized sex chromosomes cause mitotic defects (Ferree et al 2014). Our results further suggest that strong meiotic drive is not an inevitable consequence of even extensive chromosome divergence.…”
Section: Heterochromatin Divergence and Meiotic Drivesupporting
confidence: 55%
“…Our results here show that a large difference in abundance of the AATAT satellite between D. simulans and D. melanogaster chromosome 4s does not result in similarly dramatic levels of meiotic drive. We suggest that location as well as abundance influences whether satellite DNA blocks affect centromere behavior or take on neocentromere function, analogous to heterochromatin position effects that are proposed to influence whether or not circularized sex chromosomes cause mitotic defects (Ferree et al 2014). Our results further suggest that strong meiotic drive is not an inevitable consequence of even extensive chromosome divergence.…”
Section: Heterochromatin Divergence and Meiotic Drivesupporting
confidence: 55%
“…The chromosome used for the germline experiments reported here is called R(1;Y)6AX2. Its improved viability is likely a consequence of deletion or rearrangement of a portion(s) of its heterochromatin (Hinton 1955;Stone 1982;Ferree et al 2014). The relative arrangement of centromere and heterochromatic segments in this derivative has not been determined, and in the figures, the centromere and heterochromatic segments are indicated as they were in the original ring.…”
Section: Methodsmentioning
confidence: 99%
“…1). 12 Normally, this satellite exists as hundreds to thousands of tandemly repeated 359-bp monomers located primarily in a single, multi-megabase pair region or 'block' within the pericentromeric heterochromatin of the X chromosome. 14 This block spans between the centromere and the bobbed + (rDNA) locus ( Fig.…”
Section: -Bp Satellite Dna Prevents Ring Chromatid Segregationmentioning
confidence: 99%
“…Our group recently conducted a study to begin addressing these questions. 12 We performed cytological analyses of young embryos carrying 3 different X-Y rings: a highly lethal one known as Y cF #2 from Oster's original collection, 9,11 another called R(1;Y)15 that was produced more recently through FLP-FRT recombination 13 and is moderately lethal, and a third, R(1)2, which is completely nonlethal. 12 We found that bridging occurs largely through the abnormal mitotic behavior of an α-satellite known as the 359-bp repeat, which is present in all examined rings.…”
mentioning
confidence: 99%
See 1 more Smart Citation